Generation of intense terahertz radiation using optical rectification through lithium niobate and its nonlinear spectroscopy - Ang, Ray Jia Jun (Nanyang Technological University, 2020)
Terahertz phenomenology occurs in many crucial areas of Science. With photon energy in the meV range, THz radiation strikes a fine balance by having sufficient penetrating power while being non-destructive, making it superior in detection and spectroscopic techniques.